THE EUROPEAN UNION (EU)’S CHANGING FOREIGN POLICY TOWARDS ASEAN: UNDERSTANDING FROM A COMBINED LENS OF HISTORICAL INSTITUTIONALISM AND POLITICAL LEARNING - Pertiwi, Lunyka Adelina (Malaysian Journal of International Relations, 2025)
The EU approach to its foreign policy towards ASEAN has changed since 2014. This article aims to offer insights into the dynamics of the EU-ASEAN relations, particularly focusing on the EU’s foreign policy. It employs an analytical framework based on historical institutionalism and political learning to explore why and how the EU has changed its normative foreign policy to a strategic one concerning ASEAN. The analysis is initiated by examining the intensified dispute in the South China Sea demonstrating China’s more ambitious maritime policy as a pivotal moment for the EU’s perceptions towards ASEAN. The aspects of the EU’s prior experiences and internal divergence will be included to weigh into analysis. Consequently, the EU has undergone a measured shift in its political beliefs towards ASEAN but still engages with normative aspects in a subtle way. The EU has recognised ASEAN as a partner in upholding peace and stability and has started establishing connectivity through a strategic partnership.